Iot-Based Iot-Based Smart Controller (Sponcer) To Optimize Freshwater Fish Production In Pagelaran, Pringsewu, Lampung - Anggita, Rizki Devi; Styawati, Styawati (LPPM STIKI Malang, 2024)
An Internet of Things (IoT) based control system for optimal fish production in Pagelaran, Pringsewu, Lampung is a modern fish farming solution that uses IoT technology to automatically monitor and assess various fish environmental parameters. The system is equipped with various sensors that can measure critical parameters such as water level, pH, turbidity, and water temperature. This data is sent in real-time to a web-based application, allowing users to continuously monitor conditions remotely through devices connected to the internet. This helps maintain ideal fish environmental conditions for growth, reduces the risk of disease, and increases productivity. One of the striking features of this system is its automatic feed regulation capacity. With this system, feed is provided timely and accurately according to the needs of the fish, which is very important to ensure optimal growth. The purpose of developing an IoT-based system in Pagelaran, Pringsewu, Lampung is to increase productivity and fish production in the area. It is expected that with more careful monitoring and wiser feed handling, fish production can be increased in terms of both quantity and quality. In short, IoT-based system controllers not only improve operational efficiency but also reduce environmental damage. Farmers can reduce excessive resource use and lower operational costs by minimizing manual intervention and using technology for smarter pond management. It is expected that this system will become a model for more modern, efficient, and environmentally friendly fish farming practices, not only in Pagelaran, Pringsewu, Lampung but also in other areas.